Analysis of Students Analytical and Intuitive Thinking Skills in Series and Parallel Teaching Aids - Malahayati, Malahayati; Fauzan Amsal, Alfi; Amsal, Azhar; Baihaqi, Baihaqi; Ibnu Yasa, Ghufran; Malia, Rezqi (Phi: Jurnal Pendidikan Fisika dan Terapan, 2024)
Thinking is a process in which a person recalls existing knowledge from their memory and uses it to receive, process, and conclude information. Intuitive thinking is part of the logical aspect that develops a person's ability to analyze problems spontaneously, quickly, and accurately. Analytical thinking is a systematic or structured thinking activity that can effectively identify problems to be faced. The researcher used a qualitative method with a descriptive type. In this research stage, the researcher used test instruments in the form of essay test questions. The subjects targeted in this study were 6 students. The results of the study showed a comparison of the students' thinking skills: out of 6 students, 4 had intuitive thinking skills amounting to 67%, and 2 had analytical thinking skills amounting to 33%. The conclusion of this study is that students are more dominated by intuitive thinking skills than analytical thinking skills.